E항원음성 만성간염환자에서 NUC치료를 중단한 이후의 재발율 - Kim, Young Jip (The Graduate School, Ajou University, 2013)
Durability after discontinuation of nucleos(t)ide therapy in chronic HBeAg negative hepatitis patients Background: Relapse has been reported after stopping Nucleos(t)ide (NUC) therapy in the majority of chronic HBeAg negative hepatitis patients. However, the ideal treatment duration of HBeAg negative chronic hepatitis B (CHB) is not well known. We investigate the frequency of relapse rate in HBeAg negative CHB patients receiving NUC therapy. Methods: The NUC therapy was discontinued at least three times undetectable level of HBV DNA leave 6months space in 45 patients. (25 with entecavir, 14 with lamivudine, 6 with adefovir.) All patients had followed up at least 1 year after stopping NUC therapy. Serum ALT, AST and HBV DNA levels were measured every 3 months. Clinical relapse was defined as HBV DNA>2,000 IU and ALT or AST > 2 times of upper limit of normal range. Virological relapse was defined as HBV DNA>2,000 IU Results: Clinical relapse developed in 16 (35.6%) and 24 (53.3%) patients after stopping therapy at 6 months and 12 months off therapy, respectively. Virological relapse developed 22 (48.9%) and 33 (73.3%) patients at 6 months and 12 months off therapy. The factors such as age, gender, cirrhosis, baseline AST, ALT, HBV DNA levels, treatment duration, and consolidation duration were analyzed to investigate the predictive factors associated with 1 year sustained response. Of these factors, cirrhosis (86.1% in CHB, 22.2% in LC) were significantly associated with 1 year virological relapse. baseline HBV DNA and Total treatment duration tended to be associated with virological relapse. Conclusions: Virological relapse developed in the majority (73.3%) of HBeAg negative CHB patients and clinical relapse developed in the half (53.3%) of patients at 1 year off therapy. Cirrhosis was found to be associated with the low rate of virological relapse.
학위논문(석사)아주대학교 일반대학원 :의학과,2013. 8
Keywords: chronic hepatitis B; durability; nucleos(t)ide analogue